2017
DOI: 10.1186/s40816-017-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Dennettia tripetala ameliorates liver and kidney damage caused by multiple exposures to carbon tetrachloride

Abstract: Background: Dennettia tripetala is a medicinal plant with in vitro antioxidant activities. It is capable of protecting the liver and kidney of rats from damage when administered prior to a single exposure of carbon tetrachloride. The aim of this study was to document the possible ameliorative effect of the aqueous extract of Dennettia tripetala fruits on rats subjected to multiple exposures of carbon tetrachloride. Methods: Carbon tetrachloride was administered orally to male albino rats of Wistar strain four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Histopathological images from the present study showed that the aqueous and ethanolic extracts of D. tripetala caused a negligible amount of congestion in the centrioles of the liver but were not in any other way toxic to the liver, kidney, or heart of the rats. The slight congestion caused by the extracts to the centriole of the liver has been previously observed by our research group where the extract in an attempt to clear steatosis caused by the hepatorenal toxicant carbon tetrachloride induced a sort of “side effect” which featured patchy congestions of the centriole of the liver (Iseghohi & Orhue, ). In conclusion, a 28‐day administration of D. tripetala extracts does not cause considerable alterations to the organs and cells of normal healthy rats.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Histopathological images from the present study showed that the aqueous and ethanolic extracts of D. tripetala caused a negligible amount of congestion in the centrioles of the liver but were not in any other way toxic to the liver, kidney, or heart of the rats. The slight congestion caused by the extracts to the centriole of the liver has been previously observed by our research group where the extract in an attempt to clear steatosis caused by the hepatorenal toxicant carbon tetrachloride induced a sort of “side effect” which featured patchy congestions of the centriole of the liver (Iseghohi & Orhue, ). In conclusion, a 28‐day administration of D. tripetala extracts does not cause considerable alterations to the organs and cells of normal healthy rats.…”
Section: Discussionsupporting
confidence: 62%
“…The fruits were sliced and sun‐dried, then ground to fine powder. Aqueous and ethanolic extracts of the fruits were prepared following the method of Iseghohi and Orhue (), with the ethanolic extract made by soaking the plant powder in ethanol rather than water. For administration to animals, each of the resulting extracts (concentrated with a freeze dryer) was suspended in distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study investigated the ability of the ethanolic extract of the root of D. tripetalato inhibit lipid peroxidation in frozen heart muscle slices and the extract showed significantly (p < 0.05) higher antioxidant effect when compared with vitamin C which suggest that the root extract of D. tripetalais rich in antioxidants and can be used to enhance the preservation of frozen meat (28). Recent studies carried out by Iseghohi and Orhue, (29,30) revealed that administration of aqueous and ethanolicextracts of D.tripetala fruit prevent an increase in the plasma activity of GGT, alanine transaminase (ALT) and alanine phosphatase (ALP) by combating the oxidative stress associated with tetrachloromethane (CCl4) metabolism.…”
Section: Effect On Oxidative Stress and Antioxidant Activitiesmentioning
confidence: 98%
“…The use of Dennettia tripetala fruit, seed and stem for medicinal purposes has been attributed to the presence of phytochemicals, like tannins, alkaloid, steroid, flavonoids, cardiac glycosides, saponins and terpenoids [10,11]. The presence of these phytochemicals have been widely reported to possess antibiotic [12,13], antioxidant [1,14,15], anti-inflamatory [3,16] potentials. The hypoglyceaemic, analgesic, hypolipidaemic and haematoxic effects of Dennettia tripetala fruits have been reported [17][18][19].…”
Section: Introductionmentioning
confidence: 99%